Class I myosin Myo1e regulates TLR4-triggered macrophage spreading, chemokine release, and antigen presentation via MHC class II - Wenzel, Jens; Ouderkirk, Jessica L.; Krendel, Mira; Lang, Roland (European Journal of Immunology, 2015)
TLR-mediated recognition of microbial danger induces substantial changes in macrophage migration, adherence, and phagocytosis. Recently, we described the LPS-regulated phosphorylation of many cytoskeleton-associated proteins by phosphoproteomics. The functional role of these cytoskeletal and motor proteins in innate immune cell responses is largely unexplored. Here, we first identified both long-tailed class I myosins Myo1e and Myo1f as important contributors to LPS-triggered macrophage spreading. Mouse bone marrow-derived macrophages and DCs deficient in Myo1e selectively secreted increased amounts of the chemokine CCL2. In addition, the cell surface expression of MHC class II (MHC-II) on both cell types was reduced in the absence of Myo1e. However, transcriptional changes in CCL2 and MHC-II were not observed in the absence of Myo1e, indicating that Myo1e regulates specific intracellular transport processes. The capacity of macrophages and DCs lacking Myo1e to stimulate antigen-specific CD4(+) T-cell proliferation was impaired, consistent with the reduced MHC-II surface protein levels. Surprisingly, in Myo1e-deficient DCs, the proteolytic cleavage of endocytosed antigen was also increased. Together, our results provide evidence for a non-redundant function of the motor protein Myo1e in the regulation of TLR4-controlled, cytoskeleton-associated functional properties of macrophages and DCs, and in induction of a full MHC-II-restricted adaptive immune response.
EVALuna2:7660

Enhancing automated micrograph-based evaluation of LPS-stimulated macrophage spreading - Held, Christian; Wenzel, Jens; Wiesmann, Veit; Palmisano, Ralf; Lang, Roland; Wittenberg, Thomas (Cytometry Part A, 2013)
To evaluate macrophage spreading in immunofluorescence images of macrophages for surface protein CD11b and nuclear counterstaining with DAPI, it is necessary to measure the size of the macrophages at different time points after stimulation. Manual evaluation of fluorescent micrographs is usually a time-consuming and error-prone task, with poor reproducibility. Automatic image analysis methods can be used to improve the results. The quality of the analysis with these methods mainly depends on the quality of the image segmentation. A segmentation and quantification scheme based on shading correction, k-means clustering, and fast marching level sets has been developed for the purpose. An initial application of this approach showed that separating touching and overlapping cells in particular suffers severely in the inevitably blurred conditions, leading to partly erroneous measurements of macrophage spreading. An alternative method of segmentation in fluorescent micrographs was therefore investigated and evaluated in this study. The proposed approach uses a methodology that separates foreground objects from background objects on the basis of Boykov's graph cuts. In this process, a rough estimation of background pixels is used for background seeds. To identify foreground seeds, a difference of Gaussian band pass filter based workflow is developed. Information on foreground and background seeds is then used for a gradient magnitude based graph cut resulting in a robust figure-ground separation method. In addition, a fast marching level set approach is used in the post-processing step, which makes it possible to split touching cells by incorporating information about the cell nuclei. An evaluation based on a total of 553 manually labeled macrophages depicted in 21 micrographs showed that the proposed method significantly improves segmentation and splitting performance for fluorescent micrographs of LPS-stimulated macrophages and reduces the rate of error in automated analysis of macrophage spreading in comparison with alternative methods. © 2013 International Society for Advancement of Cytometry.
UnivIS-Import:2015-04-14:Pub.2013.tech.IMMD.IMMD9.enhanc
Keywords: Fluorescence Microscopy; Image Processing; Computer Assisted Microscopy

Measurement of TLR-induced macrophage spreading by automated image analysis: Differential role of Myd88 and MAPK in early and late responses - Wenzel, Jens; Held, Christian; Palmisano, Ralf; Teufel, S.; David, Jean Pierre; Wittenberg, Thomas; Lang, Roland (Frontiers in Physiology, 2011)
Sensing of infectious danger by toll-like receptors (TLRs) on macrophages causes not only a reprogramming of the transcriptome but also changes in the cytoskeleton important for cell spreading and motility. Since manual determination of cell contact areas from fluo-, rescence micrographs is very time-consuming and prone to bias, we have developed and tested algorithms for automated measurement of macrophage spreading. The two-step method combines identification of cells by nuclear staining with DAPI and cell surface staining of the integrin CD11b. Automated image analysis correlated very well with manual annotation in resting macrophages and early after stimulation, whereas at later time points the automated cell segmentation algorithm and manual annotation showed slightly larger variation. The method was applied to investigate the impact of genetic or pharmacological inhibition of known TLR signaling components. Deficiency in the adapter protein Myd88 strongly reduced spreading activity at the late time points, but had no impact early after LPS-stimulation. A similar effect was observed upon pharmacological inhibition of MEK1, the kinase activating the mitogen-activated protein kinases (MAPK) ERK1/2, indicating that ERK1/2 mediates Myd88-dependent macrophages spreading. In contrast, macrophages lacking the MAPK p38 were impaired in the initial spreading response but responded normally 8-24 h after stimulation. The dichotomy of p38 and ERK1/2 MAPK effects on early and late macrophage spreading raises the question which of the respective substrate proteins mediate(s) cytoskeletal remodeling and spreading. The automated measurement of cell spreading described here increases the objectivity and greatly reduces the time required for such investigations and is therefore expected to facilitate larger throughput analysis of macrophage spreading, e.g., in siRNA knockdown screens. © 2011 Wenzel, Held, Palmisano, Teufel, David, Wittenberg and Lang.

Using multimodal information for the segmentation of fluorescent micrographs with application to Virology and microbiology - Held, Christian; Wenzel, Jens; Webel, Rike; Marschall, Manfred; Palmisano, Ralf; Wittenberg, Thomas; et al. (Proc*s 2011 Annual International Conference of the IEEE Engineering in Medicine and Biology Society,EMBC, 2011)
In order to improve reproducibility and objectivity of fluorescence microscopy based experiments and to enable the evaluation of large datasets, flexible segmentation methods are required which are able to adapt to different stainings and cell types. This adaption is usually achieved by the manual adjustment of the segmentation methods parameters, which is time consuming and challenging for biologists with no knowledge on image processing. To avoid this, parameters of the presented methods automatically adapt to user generated ground truth to determine the best method and the optimal parameter setup. These settings can then be used for segmentation of the remaining images. As robust segmentation methods form the core of such a system, the currently used watershed transform based segmentation routine is replaced by a fast marching level set based segmentation routine which incorporates knowledge on the cell nuclei. Our evaluations reveal that incorporation of multimodal information improves segmentation quality for the presented fluorescent datasets. © 2011 IEE
UnivIS-Import:2015-04-14:Pub.2011.med.IKMI.LHMMIPDR.usingm
Keywords: Fluorescence Microscopy; Digital Pathology; image analyis